THE IMPORTANCE OF TECHNICAL AND TACTICAL PREPARATION IN BOXING : THE IMPORTANCE OF TECHNICAL AND TACTICAL PREPARATION IN BOXING - Xonturayev, Nodir; Husanova, Sahobat (Физическое воспитание, спорт и здоровье, 2025)
It is clear that techniques and tactics are how boxers move their bodies to achieve certain targets and it promote high performance and reduces the risk of injury as using good technique in boxing is beneficial and of paramount importance, and boxers need to cultivate that skill to perform the movements of their sport correctly. Thus, this article covers information about the importance of technical and tactical training in boxing.